Ice Drift in the Central Part of the Arctic Ocean (Dreif Ldov v Tsentralnoi Chasti Severnogo Ledovitogo Okeana) - Gordienko, P. A. (1960)
Ice displacements in the Arctic Ocean are analyzed with respect to direction and speed in various sectors of the ocean, taking into consideration the essential components of ice drift, such as wind drift, currents, their fluctuations and shifts, atmospheric conditions, and other factors. The analysis is based on observational data concerning the drift of the Soviet North Pole stations, notably NP-3, NP-4 and NP-5 in 1954-1955. In conclusion, the prospects and accuracy in forecasting the ice movements and conditions that affect navigation on the Northern Sea Route are evaluated. Trans. of Problemy Severa (USSR) n1 p5-29 1958, by M. Slessers. Also available as TT-60-23766.